Pengembangan video Animasi Berbasis Prezi dalam Model Discovery Learning untuk Meningkatkan Minat dan Hasil Belajar Peserta Didik pada Materi Pokok Reaksi Oksidasi Reduksi - Nasir, Normalia; Anwar, Muhammad; Sanusi, Wahida (Chemistry Education Review (CER), 2024)
This study aims to examine: (1) the process of developing Prezi-based animated video media in the Discovery Learning Model and (2) the validity, practicality, and effectiveness of Prezi-based animated video media in the Discovery Learning Model. This type of research is Research and Development (R&D), which research procedures following the development of ADDIE. The results of the study show that the validity of Prezi-based animated video media in the Discovery Learning Modelon Oxidation Reduction Reaction material is declared valid and feasible to be used. The finding is based on the validation results by expert validators with a validation value of 3.40 or in valid category. Prezi-based animated video media concluded to be practical and effective because the practicality test of Prezi-based animated video media is related to (1) the implementation in the Discovery Learning Modelis at an average value of M = 1.98 in the category (1.5 ≤ M ≤ 2.0) which means that the aspects and criteria observed are in fully implemented category, (2) the teacher’s response with a percentage of 87.50% with a very practical category and students’ responses with a percentage of 90.20% with a very practical category. Prezi-based animated video media also meets the effective criteria with the results of (1) an increase in students' learning interest from 55.11% to 74.14%, (2) the completeness or achievement of KKM who obtained a score above 75 is 20 people (86.95%) which overallis declared to meet the minimum subject completeness criteria.